Penanganan Kurangnya Perhatian Orang Tua pada Perilaku Anak Usia Dini - Yusi Desia Ananta (Pusat Riset dan Inovasi Nasional, 2025)
The development of children's attitudes and behavior is a learning process to know about morals and ethics, as an effort to support the development of children's behavior, attention and guidance provided by parents is needed. At the age of 4-5 years, children are still starting a developmental stage that their parents must pay attention to. In this stage of development, parents play a very important role in stimulating children's development, especially in the development of children's behavior. Children need sufficient attention and affection from parents for optimal growth and development. However, parents' busy work often results in reduced time spent with their children. As a result, children receive less attention and affection that they should receive. Children who don't get enough attention from their parents are at risk of having deviant behavior such as stealing, making trouble, speaking harshly, swearing or bullying. This negative behavior arises because children feel neglected and try to get attention through these methods.